ANALISA PENURUNAN RAFT-PILED FOUNDATIONAREA BOGIE WAREHOUSE PROYEK JAKARTA LRT SECTION DEPOT - Amelia Wijaya; Aksan Kawanda (Universitas Trisakti, 2018)
The foundation of the raft post is the bottom structure of a building that channeled the load from the structure over the soil under it. Carrying capacity of drill pile foundation is influenced by the capacity of the pole tipand bearing capacity of the pole blanket. The decline in this area can be an immediate decline and a decrease in consolidation. This study aims to analyze the decrease of raft poles and the proportion of load bearing in the bogie area of the Kelapa Gading LRT warehouse depot - Jakarta. From the analysis of theNSPT test results in the field, the ultimate carrying capacity and the decrease that occurred on the raft poles were obtained. Based on the results of calculation of the ultimate carrying capacity of a single drill pole of 1.1 x 104 kN and the carrying capacity of the group is 1.1 x 108 kN. Calculation of group efficiency with the Feld method is obtained at a value of 0.588. In the calculation of the immediate decline of the pole, a value of 5 cm is obtained and a decrease in consolidation of 7 cm. From the calculation of the proportion of raft poleload bearing the value of Pr = 6 x 10-6 is obtained, which means that load bearing can be said to be dominated by rafts.